2019
DOI: 10.1155/2019/8586153
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Mental Health Conditions of Patients with Opioid Use Disorder

Abstract: Objectives Noninvasive estimation of cortical activity aberrance may be a challenge but gives valuable clues of mental health in patients. The goal of the present study was to characterize specificity of electroencephalogram (EEG) electrodes used to assess spectral powers associated with mental health conditions of patients with opioid use disorder. Methods This retrospective study included 16 patients who had been diagnosed with opioid use disorder in comparison with 16 sex- and age-matched healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…It has been suggested that adjacent electrodes are functionally coherent although such relationship for two distant electrodes, particularly at different cortical subregions, does not exist [29,30]. Findings that EEG amplitudes of adjacent electrodes were at the same level [18] support the coherent hypothesis. This suggests that, despite different electrodes but physical adjacency, their spectral powers could be grouped to determine functional changes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been suggested that adjacent electrodes are functionally coherent although such relationship for two distant electrodes, particularly at different cortical subregions, does not exist [29,30]. Findings that EEG amplitudes of adjacent electrodes were at the same level [18] support the coherent hypothesis. This suggests that, despite different electrodes but physical adjacency, their spectral powers could be grouped to determine functional changes.…”
Section: Discussionmentioning
confidence: 92%
“…Only one time of data prior to rehab treatment was approved by the IRAs to be used in the present study. EEG data were downloaded from the database as described previously [18]. Briefly, raw data was edited using the editing tool within the NeuroGuide software to remove physical artifacts (including eye movement, jaw movement, and gross movement) and was then visually inspected.…”
Section: Eeg Data Analysis and Rationale For Five Distinct Approachesmentioning
confidence: 99%
“…We intended to focus on the frontal regions since previous studies have shown that activity in the regions was significantly associated with empathic responses and pain perception (Rameson et al, 2012;Morelli et al, 2014). These seven electrodes are associated with the frontal regions (Minnerly et al, 2019) and were used as the foci of statistical analyses.…”
Section: Erp Analysismentioning
confidence: 99%
“…EEG data were downloaded from the database as described previously (Minnerly et al, 2019). Briefly, raw data was edited using the editing tool within the NeuroGuide software to remove physical artifacts (including eye movement, jaw movement, and gross movement) and was then visually inspected.…”
Section: Eeg Data Analysis and Rationale For Five Distinct Approachesmentioning
confidence: 99%
“…By analysis of delta/δ, theta/θ, alpha/α, beta/β, and gamma/γ waves, it was found that all of the five spectral powers was 71 elevated with almost equipotency in the frontal, central, temporal, parietal, and occipital 72 subregions of patients with OUD (Wang et al, 2015). However, others demonstrated that it was only certain spectra, but not all, that were elevated in the cortical subregions (Polunina & Davydov, 2004;Greenwald & Roehrs, 2005;Motlagh et al, 2018;Minnerly et al, 2019). The selective effects are also reported in MUD and AUD.…”
Section: Introductionmentioning
confidence: 99%